3D-printed smartphone-based device for label-free cell separation. Issue 3 (July 2017) - Amin, Reza; Knowlton, Stephanie; Dupont, Joshua; Bergholz, Johann S; Joshi, Ashwini; Hart, Alexander; Yenilmez, Bekir; Yu, Chu Hsiang; Wentworth, Adam; Zhao, Jean J; Tasoglu, Savas
Aim: To assess several fabrication metrics of a 3D-printed smartphone-attachable continuous-flow magnetic focusing device for real-time separation and detection of different cell types based on their volumetric mass density in high-volume samples.Method: The smartphone apparatus has been designed and fabricated using three different 3D printing method. Several 3D printing metrics including cost, printing time, and resolution have been evaluated to propose a cost-efficient and high-performance platform for low-resource settings.Results: To apply the magnetic focusing technique on large sample volumes, a heterogeneous mixture of sample (e.g., containing blood cells and cancer cells) suspended in paramagnetic medium is pumped through a magnetic field at an optimum flow rate. The performance of the 3D-printed device has been investigated by demonstrating separation of microspheres, breast, lung, ovarian and prostate cancer cells mixed with blood cells. The separation distance of cancer and blood cells is around 100 μm, allowing the two cell types to be easily distinguished.Conclusion: This device could be useful for clinical centers in low-income countries where expensive infrastructure, equipment (e.g., FACS) and technical expertise are lacking. This device could ultimately be applied to rare cell separation and purification.